(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This paper examined the impact of insecurity on Nigerian education. Secondary data were used in the paper. The secondary data were collected from print and online publications. Content analysis was employed for literature screamed in the paper. The paper concluded that insecurity has affected development of education in Nigeria. Specifically, the paper identified; reduction in education funding, reduction in private investment on education, unstable academic calendar, reduction in education manpower, led to students’ death and reduction in students’ enrolment, retention and completion. Based on this finding, the paper hereby recommends the following: Government deploy artificial intelligence to educational institutions to help in security management. Government should address the factors responsible for various forms of insecurity in order to devise a lasting solution to the problem. Government should address the high level of unemployment. Government should pay serious attention to the security of the borders against external non-stats actors and criminals. Government should strengthening prosecution and legal actions on bandits and insurgents to ensure perpetrators of offenses such as bandits, terrorism and kidnappers are brought to justice.